Biocontrol potential of Fusarium equiseti and Cladosporium cladosporoides against Aphis fabae under controlled conditions - Damian, Jedius France; Martin, Martin John; Msuya, Dunstan Gabriel (Frontiers in Agronomy, 2025)
Bean aphid is a significant insect pest that limits achievement of maximum yields and quality of beans. Overreliance on synthetic insecticides has led to the development of insecticide resistance, negatively impacting both human and environmental health. Use of entomopathogenic fungi is considered safer and environmentally friendly for managing bean aphids. A study was conducted to evaluate the effectiveness of three different conidial concentrations 1× 107, 1 × 108, and 1 × 109 spores/ml from two fungal isolates, Fusarium equiseti (JD02) and Cladosporium cladosporioides (JD07) along with distilled water containing 0.1% Triton x-100 and Imidacloprid as controls, against the Aphis fabae. A completely randomized factorial experiment was used in which petri dishes containing live aphids were sprayed with suspensions of the fungi concentrations. Mortality rate was recorded at the 3rd, 5th, and 7th days after inoculation. At the 7th day, the results showed that Imidacloprid treatment caused high mortality rates of 100%. A concentration of 1×109 spores/ml resulted in mortalities of 93.65% and 72.9%, followed by 1×108 spores/ml, which resulted in mortalities of 78.57% and 57.38% for JD-02 and JD-07, respectively. Meanwhile, a concentration of 1×107spores/ml led to lower mortalities of 62.02% and 40.24% for JD-02 and JD-07, respectively. Additionally, the LT50 and LT90 of F.equiseti and C.cladosporioides differed significantly at P<0.05; however, among the tested concentrations, 1×109 spores/ml of both F.equiseti and C.cladosporioides took 5.09 and 5.23 days to kill 50%, and 6.92 and 7.52 days to kill 90% of bean aphids, respectively. The isolate F.equiseti caused higher mortality compared to C.cladosporioides; additionally, a concentration of 1×109 spores/ml of F.equiseti resulted in higher mortality > 90% at the seventh day. Therefore, Fusarium equiseti demonstrated significant potential for controlling bean aphids.